Hubungan antara intensitas penggunaan Aplikasi TikTok dengan self-control remaja - Iis Farida Aryani; Galih Fajar Fadillah; Angga Eka Yuda Wibawa (Nur Science Institute, 2026)
TikTok has become one of the most popular social media platforms among adolescents and may be associated with their level of self-control. This study aimed to examine the relationship between the intensity of TikTok use and self-control among members of youth organization in Klarisan Village, Ampel District. The study employed a quantitative approach with a correlational design. The population comprised 110 adolescents, and 86 respondents were selected through purposive sampling. Data were collected through observation and a Likert-scale questionnaire. The research instruments were tested for validity and reliability. The Kolmogorov-Smirnov test was used to assess data normality, and Pearson's Product-Moment Correlation was used to test the hypothesis. The findings revealed a positive and significant relationship between the intensity of TikTok use and adolescents’ self-control. This indicates that higher levels of TikTok use were associated with greater self-control. These findings suggest that TikTok use is not necessarily associated with poor self-control. Therefore, family and community guidance is needed to promote healthy, purposeful, and responsible social media use.